Pengaruh Pelatihan dan Insensif terhadap Kinerja Karyawan di PT Bank Danamon Madiun - Yuliana, Rachma (Arthavidya Jurnal Ilmiah Ekonomi, 2018)
Training and intentive have large effect to employeeperformance therefore, in this research analysis the effect of thetwo variable to the employee performance. This research aims is toknow the effect of training and incentive to employeeperformance.This research use 56 employee at PT Bank DanamonMadiun, the data are collected by quwitionaire and self-completedby respondend. From the data, it analized by regression multipleanalysis to know the effect off each variable that has dominanteffect.The research result show the both training and incentivehave positive and significant effect to employee make. From thetwo variable, training variable has dominant effect to employeeperformance. It is because training is given rightly, therefore. Itcan increase employee performance at PT Bank DanamonMadiun.From the research there are two implication. First, for PTBank Danamon Madiun, in order to increase the employeeperformance of PT Bank Danamon Madiun must use the trainingand incentive rightly, especially training variable that hasdominant effect to employee performance. Second, for researchthat interested to advance the research could develop the researchto wider object to increase generalization of this research finding.Keywords : Training, Incentive, Employee performance, PT BankDanamon Madiun